Effects of flat tax reforms in Western Europe on equity and efficiency - Andreas Peichl; Alari Paulus (Finanzwissenschaftliches Forschungsinstitut an der Universität zu Köln (FiFo Köln), 2008)
The flat income tax has become increasingly popular recently, yet its implementation is limited to Eastern Europe. We analyse the distributional and e? ciency effects of flat tax scenarios for Western European countries. Our simulations show that flat tax rates required to attain revenue neutrality with existing basic allowances improve labour supply incentives. However, they result in higher inequality and polarisation. Flat rates necessary to keep the inequality levels unchanged allow for some scope for flat taxes to increase both equity and e? ciency. Our analysis suggests that Mediterranean countries are more likely to benefit from flat taxes.
Keywords: H24; D31; C81; 330; Flat tax reform; income distribution; work incentives; microsimulation; Flat Tax; Steuerreform; Steuerwirkung; Arbeitsangebot; Steuerinzidenz; Einkommensverteilung; Westeuropa